Investigating the Challenges Faced by Novice Programmers at the College of Technical Sciences – Sebha (Sebha University Conference Proceedings, 2025)
Learning Learning Learning to program is a challenging task, particularly for novice students with limited exposure to computing and the English language, which underpins most programming languages. This study investigates the specific difficulties faced by beginner programmers at the College of Technical Sciences – Sebha, where courses are taught in Arabic but programming syntax and error messages remain English-based. Using a mixed-methods approach, data were collected through a structured questionnaire administered to 59 students—most of whom were first-time programming learners. Quantitative results were supported by qualitative insights from open-ended responses. Over half of the participants (54%) identified interpreting English-language error messages as their most significant challenge. Additional issues included understanding loops, object-oriented programming, and designing structured code. Students emphasized the need for clearer explanations, more tutorial time, and improved language support. These findings suggest that programming instruction in non-English-speaking contexts should integrate bilingual strategies and scaffolded learning. Future work should explore targeted interventions to better support novice learners.